Evaluation of the Serum Level of Complement Proteins C3, C4 and Immunoglobulins IgG, IgM for some Patients with Acne Vulgaris in Baquba City - Ahmed Satar Ibraheem; Maha Falih Nazzal (Zien Journals, 2022)
This study was conducted in Baqubah Teaching Hospital/Consulting Clinic which lasted from the beginning of September 2021 to the end of February، 2022, as the study aimed to investigate the serum level of some immunological parameters in patients with acne in Diyala Governorate from these factors IgM, IgG immunoglobulins and C4, C3 complement proteins by using single Radio immunodiffusion method.
Keywords: immunological; factors; complement; lasted